A trial like ALIC4E: why design a platform, response-adaptive, open, randomised controlled trial of antivirals for influenza-like illness?. Issue 2 (8th May 2018) - Butler, Christopher C.; Coenen, Samuel; Saville, Benjamin R.; Cook, Johanna; van der Velden, Alike; Homes, Jane; de Jong, Menno; Little, Paul; Goossens, Herman; Beutels, Philippe; Ieven, Margareta; Francis, Nick; et al.
ALIC 4 E is the first publicly funded, multicountry, pragmatic study determining whether antivirals should be routinely prescribed for influenza-like illness in primary care. The trial aims to go beyond determining the average treatment effect in a population to determining effects in patients with combinations of participant characteristics (age, symptom duration, illness severity, and comorbidities). It is one of the first platform, response-adaptive, open trial designs implemented in primary care, and this article aims to provide an accessible description of key aspects of the study design. 1) The platform design allows the study to remain relevant to evolving circumstances, with the ability to add treatment arms. 2) Response adaptation allows the proportion of participants with key characteristics allocated to study arms to be altered during the course of the trial according to emerging outcome data, so that participants' information will be most useful, and increasing their chances of receiving the trial intervention that will be most effective for them. 3) Because the possibility of taking placebos influences participant expectations about their treatment, and determining effects of the interventions on patient help seeking and adherence behaviour in real-world care is critical to estimates of cost-effectiveness, ALIC 4 E is an open-label trial. A platform, response-adaptive, open trial design allows for flexibility and may enhance efficiency in determining cost-effectiveness of interventions for acute infections http://ow.ly/NODY30jACb7